Delivering clinical trials at home: protocol, design and implementation of a direct-to-family paediatric lupus trial. Issue 1 (7th May 2021) - Randell, Rachel L; Singler, Lindsay; Cunningham, Anthony; Schanberg, Laura E; Cohen-Wolkowiez, Michael; Hornik, Christoph P; Balevic, Stephen J
Abstract : Introduction: Direct-to-family clinical trials efficiently provide data while reducing the participation burden for children and their families. Although these trials can offer significant advantages over traditional clinical trials, the process of designing and implementing direct-to-family studies is poorly defined, especially in children with rheumatic disease. This paper provides lessons learnt from the design and implementation of a self-controlled, direct-to-family pilot trial aimed to evaluate the effects of a medication management device on adherence to hydroxychloroquine in paediatric SLE. Methods: Several design features accommodate a direct-to-family approach. Participants meeting eligibility criteria from across the USA were identified a priori through a disease registry, and all outcome data are collected remotely. The primary outcome (medication adherence) is evaluated using electronic medication event-monitoring, plasma drug levels, patient questionnaires and pill counts. Secondary and exploratory endpoints include (1) lupus disease activity measured by a remote SLE Disease Activity Index examination and the Systemic Lupus Activity Questionnaire; and (2) hydroxychloroquine pharmacokinetics and pharmacodynamics. Recruitment of the initial target of 20 participants was achieved within 10 days. Due to initial recruitment success, enrolment was increased to 26 participants. Additional participants who were interested were placed on a waiting list in case of dropouts during the study. Discussion and dissemination: Direct-to-family trials offer several advantages but present unique challenges. Lessons learnt from the protocol development, design, and implementation of this trial will inform future direct-to-family trials for children and adults with rheumatic diseases. Additionally, the data collected remotely in this trial will provide critical information regarding the accuracy of teleresearch in lupus, the impact of adherence to hydroxychloroquine on disease activity and a pharmacokinetic analysis to inform paediatric-specific dosing of hydroxychloroquine. Trial registration number: ClinicalTrials.gov Registry (NCT04358302 ).